Evolutionary consumer psychology: Ask not what you can do for biology, but…. Issue 3 (28th April 2013) - Kenrick, Douglas T.; Saad, Gad; Griskevicius, Vladas
Abstract: The commentaries raise questions about modularity, and about the evidence required to establish evolutionary influences on behavior. We briefly discuss evidence leading evolutionary psychologists to assume that human choices reflect evolutionary influences, and to assume some degree of modularity in human information processing. An evolutionary perspective is based on a multidisciplinary nomological network of evidence, and results of particular experiments are only one part of that network. The precise nature of, and number of, information processing systems, is an empirical question. Consumer psychologists need not retrain as biologists to profit from using insights and findings from evolutionary biology to generate new hypotheses, and to contribute novel insights and findings to the emerging nomological network of modern evolutionary science.